2022
DOI: 10.21203/rs.3.rs-2048852/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Oral bioavailability of microdoses and therapeutic doses of midazolam as a 2-dimensionally printed orodispersible film in healthy volunteers

Abstract: Purpose Use of two-dimensional (2D) printing technologies of drugs on orodispersible films (ODF) can promote dose individualization and facilitate drug delivery in vulnerable patients including children. We investigated midazolam pharmacokinetics after administration of 2D-printed ODF (EudraCT 2020-003984-24). Methods Midazolam doses of 0.03 mg and 3 mg were printed on an ODF using a 2D drug printer. We investigated the bioavailability of the two midazolam doses with ODF swallowed immediately (ODF-IS) or del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…AEs possibly related to the drug treatment 2 [7] Nasopharyngitis 2 [7] AEs likely not related to the drug treatment 4 [13] Increased blood triglycerides 2 [7] Increased blood cholesterol 1 [3] Increased blood uric acid 1 [3] Data are presented as number [%]. No AEs were reported under the fed conditions.…”
Section: Serious Aesmentioning
confidence: 99%
See 1 more Smart Citation
“…AEs possibly related to the drug treatment 2 [7] Nasopharyngitis 2 [7] AEs likely not related to the drug treatment 4 [13] Increased blood triglycerides 2 [7] Increased blood cholesterol 1 [3] Increased blood uric acid 1 [3] Data are presented as number [%]. No AEs were reported under the fed conditions.…”
Section: Serious Aesmentioning
confidence: 99%
“…Moreover, it can be easily applied by different patients as well as those who cannot easily access water (8,9). Several studies have confirmed the bioequivalence between OSF and the reference formulations (e.g., sildenafil, clobazam, riluzole, and midazolam) (10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%